Intergovernmental Grants and Policy Competition: Concepts, Institutions, and Evidence - Jeffrey Clemens; Stan Veuger (American Enterprise Institute (AEI), 2023)
Our purpose is three-fold. First, we summarize some of the core insights from both classic and more recent papers in the literature on the role of intergovernmental grants in systems of fiscal federalism. Second, we provide an updated look at some of the key institutions through which intergovernmental transfers are implemented in the United States. Third, we consider the rich environment of the COVID-19 pandemic in which new additional intergovernmental transfers were deployed, and present empirical evidence on how they affected state-level corporate tax policy. We conclude by discussing productive directions for future research on the economics of fiscal federalism and the role of intergovernmental grants as policy instruments in federal systems.
Keywords: 330